Surgical Outcomes in Macular Telangiectasia Type 2-Related Macular Holes: A Report on Four Patients - Kinza T. Ahmad; Joseph Chacko; Ahmed B. Sallam; David B. Warner; Sami H. Uwaydat (Case Reports in Ophthalmological Medicine)
Introduction. The few published studies that exist on the surgical outcomes of full-thickness macular hole (FTMH) repair in Macular Telangiectasia (MacTel) Type 2 report poor rates of hole closure of around 30%. This study is the largest case series of patients with FTMH in MacTel Type 2 and describes an 80% hole closure rate. Purpose/Aim. To describe the outcomes of four patients who underwent surgery for FTMH associated with MacTel Type 2. Methods. A retrospective review of clinical, surgical, and imaging data of five eyes in four patients with MacTel Type 2 FTMH who underwent pars plana vitrectomy (PPV) with internal limiting membrane (ILM) peeling and 30% SF6 or 15% C3F8 gas tamponade within 3-9 months of initial vision decline. Results. Visual acuity (VA) at the time of surgery ranged from 20/50 to 20/200. Successful hole closure was achieved in four out of five eyes, and final VA ranged from 20/20 to 20/40 at follow-up visits greater than 20 months postoperatively. The single eye that did not achieve hole closure had a final VA of 20/60. Conclusion. Our case series describes higher hole closure rates and better final VA than previously published reports for macular hole surgery in patients with MacTel Type 2 FTMH.